QUANTITATIVE INDICATORS OF THE ACQUISITION OF TOURISM TERMS - Ashurov Nurbek Oybek o‘g‘li (Western European Studies, 2024)
In this article, the specific features of the processes of development of scientific knowledge are clearly reflected in the linguistic landscape of the world, in particular, in terminology. That is why experts emphasize that the object of anthropological research should be the lexical systems of different languages, primarily terminology.
Keywords: conductor; booking; commute; Pullman car